EKSISTENSI INTERNATIONAL CRISIS GROUP DALAM PERKEMBANGAN GERAKANTERORISME DI INDONESIA STUDIKASUS: GERAKAM JEMAAH ISLAMIYAHTAHUN 2002-2015 - Asnawi, Amelia; Fachri, Yuli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explains how the existence of an international non-governmental organizations in providing tendentious reports about the development of Jemaah Islamiyah in Indonesia.International crisis group is a non-governmental organization whose mission is to prevent and resolve conflicts through analysis based on field dangerous high-level advocacy and analysis made by the courts.in its report, titled Al-Qaeda in Southeast Asia: the case of the Ngruki network in Indonesia, making Indonesia into a corner because, according to the report of international crisis group claimed Indonesia as a center for the development of terrorism the biggest in Southeast Asia because it has links with al-Qaeda.Sidney Jones as director of the International Crisis Group in Indonesia have strong reasons related to the development of the movement Jemaah Islamiyah in Indonesia because of the strong organizational structure and ideology of Jemaah Islamiyah who embrace the ideologysalafiah.